Modelling within a self-organising or a microsimulation framework: opposite or complementary approaches? - Lena Sanders (Unité Mixte de Recherche 8504 Géographie-cités, 1999)
In this note I will shortly focus on the question of scale in the modelling of populations’ spatial mobility. Let us simply consider the case of three organisational levels : at the top, a region as a whole, for instance a country or a group of countries (macro-level), at an intermediate level a set of spatial units, for example the departments or the communes (meso-level) and at the bottom the individuals (micro-level). The question is, for a specific problem, to choose the most adapted level to develop a model. In many circumstances, there is no ambiguity, the level is induced by the problem. But in other cases, there is a possible choice. For example, if one wants to understand and to simulate the spatial redistribution of the population within a regional system during a certain period of time, the result of the model is expected to be given at a meso-level, but the model can be developed either within the framework of microsimulation, or within that of synergetics, each implying its proper philosophy. One privileges hypotheses on individuals’ behaviour, the other focuses on processes that refer to a meso-level logic. The aim here is to underline what conceptual differences are induced by these two approaches.